Obstacles and Needs of Anesthesia Residents towards Research Supporting System in the Faculty of Medicine Ramathibodi Hospital, Mahidol University - Komonhirun, Rojnarin (Thai Journal of Anesthesiology, 2021)
Background: Research in Anesthesiology Residency Program is developed to increase knowledge and clinical experience. This study aimed to describe obstacles and needs of the residents in supporting research participation during residency training program. Methods: We conducted a survey among all residents in the program (N=51). The questionnaire comprised questions of demographic data, levels of research interest, the obstacles to research and the possible supports that are needed. Descriptive and correlational statistics were analysed. Results: Forty-one anesthesiology residents (80.39%) participated in this study. Mean age was 28.37±1.39 years. Most of them were female (n=33). Sixteen, thirteen and twelve participants were in the 1st, 2nd and 3rd year residency training, respectively. The average scores of advisor’s attentiveness and residents’ interest towards research were 8.1±2.12 and 7.22±1.88, accordingly. ‘Having little research skills’ was the highest rated obstacle (score 4.33), whereas ‘writing protocol or manuscript in valid English’ was the highest rated need to support (score 4.16). Conclusion: Lack of research skills was the key obstacle on doing research. Furthermore, most residents required English skills support for manuscript writing.